Dietitian-observed macronutrient intakes of young skill and team-sport athletes: Adequacy of pre, during, and postexercise nutrition - Baker, L. B.; Heaton, L. E.; Nuccio, R. P.; Stein, K. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Sports nutrition experts recommend that team-sport athletes participating in intermittent high-intensity exercise for =1 hr consume 1-4 g carbohydrate/kg 1-4 hr before, 30-60 g carbohydrate/hr during, and 1-1.2 g carbohydrate/kg/hr and 20-25 g protein as soon as possible after exercise. The study objective was to compare observed vs. recommended macronutrient intake of competitive athletes under free-living conditions.